Creative Accounting on Audit Delay: Transparency of Profit Rights and Equity Distribution As Moderation - Agustin, Beby Hilda; Marhaendra Kusuma; Pramiana, Omi; Santos , Alfredo Dos (Fakultas Ekonomi Universitas Kadiri, 2025)
The purpose of this study is to provide evidence whether: 1) creative accounting actions have a positive effect on audit delay, and 2) whether transparency of distribution of rights to shareholders weakens the positive effect of creative accounting on audit delay. Financial report data with 2,641 observation data from a sample of 543 companies listed on the IDX for the period 2020-2024 were tested using Moderated Regression Analysis. The results of the study indicate that creative accounting has a positive effect on audit delay and transparency of distribution of rights to shareholders weakens this positive effect. Auditors need additional audit resources to ensure whether financial reporting is the result of creative accounting actions. Transparency of distribution of rights to shareholders weakens this positive effect because it encourages shareholders to be involved in monitoring their interests in profit rights and net asset rights. The originality of this study is testing the moderating role of transparency of distribution of rights to shareholders in the effect of creative accounting on audit delay